Dealing with Situations of Positive and Negative Washback - Melita Djurić (Scripta Manent)
The article deals with the complexity of a washback phenomenon in language testing. It focuses on its positive effects within an institution as well as on the situations of negative washback. Washback is presented as a stimulus for a change and as a bridge for efficient communication between teachers and testers. Certain changes as a result of positive washback point at the opportunities which a testing institution has when it organizes, designs and administers criterion-referenced tests.